Tamarix articulata Extracts Exhibit Antioxidant Activity and Offer Protection against Hydrogen Peroxide-Mediated Toxicity to Human Skin Fibroblasts - Abdullah M. Alnuqaydan (Journal of Toxicology)
Tamarix articulata (TA) is a wild halophytic plant growing in extremely harsh environmental conditions in the deserts of Saudi Arabia. Evaluating the protective effect of the methanolic extract of different parts (fresh and dry leaves, stem, and root) of TA was determined by MTT assay using Hs27 skin fibroblasts as the cellular model. The study was designed and conducted in two sets. The first set assesses the toxicity profile of TA extracts in both concentration- and time-dependent ways on Hs27 cells. Our MTT results showed that methanolic extracts from all four parts of TA at varying doses (27.5, 55, 110, and 220 μg/mL) display negligible toxicity when exposed for 4 h. However, exposure of Hs27 cells to varying doses of all four TA extracts for 24 and 48 h promotes significant 23%, 24%, 26%, and 25% p<0.05 and 35%, 36%, 39%, and 41% p<0.05 cell toxicity at 220 μg/mL of all four TA extracts compared to untreated control cells. To evaluate the protection offered by TA extracts against H₂O₂, we perform a second set of experiments to preincubate Hs27 cells with the TA extracts in both dose- and time-dependent way. This is followed by 300 μM hydrogen peroxide- (H₂O₂-) mediated oxidative insult for 1 h. Using MTT assay, we found that methanolic extracts of TA at different time points (4, 24, and 48 h) and higher doses (220 μg/mL) provide significant protection in cell viability when challenged with H2O2-induced oxidative stress in Hs27 cells. The protective effect was more pronounced at 48 h and 220 μg/mL and the amounts were 39%, 41%, 41%, and 44% for stem, root, fresh leaf, and dry leaf TA extracts p<0.05, respectively, compared to untreated cells (2–4%). Collectively, the current study demonstrates that methanolic extracts of TA contain potential bioactive compounds and offer significant protection against H2O2-mediated oxidative stress in Hs27 skin fibroblasts.